PERTANGGUNG JAWABAN PANITIA PENYELENGGARA KONSER MUSIK TERHADAP PENONTON YANG MEMBELI TIKET SECARA ONLINE - Saputra, Hendrik Aldi; Pasaribu, Benhard Kurniawan (LPPM STIH Awang Long, 2024)
A music concerts are business prospects int the filed of entertainment, which can be held in various places because of promising business oportinity in there. A music concert Music concerts require careful planning, good organization, and implementation in accordance with the schedule that has been determined, therefore the organizers are obliged to fulfill their rights and obligations to consumers or in this case music concert goers. In this study the authors will raise two problems, namely how the legal protection of consumers who buy tickets online, and how the problem resolution efforts by the organizing committee of the music concert to the audience who buy tickets online. This study using normative legal research, of whom the data used in this study are library material, namely material that contains new or cutting-edge scientific knowledge, or a new understanding of facts that are known or about Ideas (Ideas), in this case covering books, journals, dissertations or theses and other legal materials. This study of normative legal materials fully uses premier legal materials and secondary legal materials. This study concludes that online concert ticket buyers have the right to get goods and/or services, specifically the ability to access the musical venue in accordance with the claimed exchange value, conditions, and guarantees. The concert organizer's failure to allow online ticket buyers into the musical venue constitutes a breach of contract for which restitution can be sought through either litigation or non-litigation procedures.